Electronic Money: Consumer Protection Versus Legal Asymmetric Information - Maulana, Ryan; Murwadji, Tarsisius; Litai, Helza Nova (Journal of Cultural Analysis and Social Change, 2026)
The writing of the article is related to the problem of E-toll card consumer protection caused by the regulations governing it, namely the Bank Indonesia Regulation (PBI) dealing with asymmetric information. In Bank Indonesia Regulation Number 11/12 of 2009 concerning Electronic Money in Article 1, what is meant by: Electronic Money is a payment instrument that fulfills the following elements: a. issued on the basis of the value of money deposited in advance by the holder to the issuer; b. the value of money is stored electronically in a medium such as a server or chip; c. used as a means of payment to merchants who are not the issuer of the electronic money; and d. the value of electronic money deposited by the holder and managed by the issuer is not a deposit as referred to in the law governing banking. This article is the most crucial article in terms of consumer protection. Mechanically, the issuance of an E-toll card is the same as the issuance of a passbook. The difference is that there is no filling out of the E toll application form so that the E-toll card holder's data is not contained in the issuer's administration. This is the main problem causing the failure of consumer protection because cardholders are not legal standing, i.e. litigants in court. The placement of financial data in the server and the issuer's refusal that the deposit is not a deposit causes the issuer to be irresponsible is an unlawful act by the regulator. This is what the author calls legal asymmetric information.